2020
DOI: 10.1159/000509945
|View full text |Cite
|
Sign up to set email alerts
|

Cryostorage to What End? – Autologous Stem Cell Products in Burkitt Lymphoma, Acute Lymphoblastic Leukemia, Acute Myeloid Leukemia, and Myeloproliferative Neoplasm Patients

Abstract: <b><i>Introduction:</i></b> Recently, we identified a huge discrepancy between the collection practice and the actual utilization of cryopreserved peripheral blood stem cells (PBSCs) for high-dose chemotherapy (HDCT) and autologous blood stem cell transplantation (ABSCT). Specifically, patients with Burkitt lymphoma, acute leukemia, and myeloproliferative neoplasms (MPN) were frequently not referred for ABSCT after successful PBSC collection. <b><i>Objective:</i></b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…The German prospective, multicenter, open-label, non-interventional OPTIMOB study addressed this lack of knowledge by analyzing mobilization and collection parameters in a large cohort of adult, transplant-eligible, good and poor mobilizing patients with lymphoma or multiple myeloma. In this special issue, the results of this huge national study with 28 recruiting study centers are presented in two articles: Bittrich et al [8] described the results in patients with multiple myeloma, whereas Kriegsmann et al [9] showed the results of the cohort of lymphoma patients.…”
mentioning
confidence: 99%
“…The German prospective, multicenter, open-label, non-interventional OPTIMOB study addressed this lack of knowledge by analyzing mobilization and collection parameters in a large cohort of adult, transplant-eligible, good and poor mobilizing patients with lymphoma or multiple myeloma. In this special issue, the results of this huge national study with 28 recruiting study centers are presented in two articles: Bittrich et al [8] described the results in patients with multiple myeloma, whereas Kriegsmann et al [9] showed the results of the cohort of lymphoma patients.…”
mentioning
confidence: 99%